KERAPATAN KELURUSAN SUNGAI DI WILAYAH MAJALENGKA DAN HUBUNGANNYA DENGAN VARIABEL MEKANIKA TANAH: SUDUT GESER-DALAM - Zakaria, Zufialdi; Sophian, Irvan (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
Areas of the research include the role in The Eastern Zone of Bogor Basin. In this research are Research areas included in the Eastern zone Bogor Basin. In this research are discussed: 1) The role of tectonic and drainage lineament on Tertiary and Quaternary rocks in the study area; 2) The role of soil variables that are part of the parent rock material. The method used is a probabilistic analysis involving friction angle and lineament densty. The results showed: 1) The absence of differences in the direction of linemament drainage patterns on Tertiary and Quaternary rocks, indicating the influence of the deformation of the same, namely the upligt, the two rocks together to experience the rapture; 2) The density llinemanet associated with one variable, namely internal friction angle (phi). Internal friction angle (phi) decreases with increasing density lineament.